Enzim suplementation in the quail (Coturnix coturnix Japonica) diet containing Indigofera Zolingeriana on performance and metabolizable energy - Suharyanti, Suharyanti; Ridla, Muhammad; Wijayanti, Indah; Mutia, Rita (Faculty of Animal Science, Universitas Brawijaya, 2021)
This study aims to evaluate the effect of protease enzyme supplementation and NSP on feed containing I. Zollingeriana to improve performance and metabolic energy in quails. This study used 192 female quails with a Coturnix-coturnix japonica strain aged 42 days. The experimental design used in this study was a completely randomized design (CRD), with four treatments and four replications, with treatments being R1 = Basal Feed, R2 = Feed containing 10% I. Zollingeriana, R3 = R1 + protease enzyme, and R4 = R1 + NSP enzyme. The parameters observed in this study were feed consumption, hen day, egg mass production, feed conversion, mortality, and metabolic energy. The results showed that feeding containing 10% of I. Zollingeriana was able to increase the consumption, decrease the egg mass production, increase feed convertion and reduce the nitrogen retention.Â The addition of the NSP enzyme can increase quil performance which were fed containing 10% I. Zollingeriana. The use of NSP and protease enzymes can increase the retention value of quail ration containing I. Zollingeriana leaves.